Targeting the insulin-like growth factor-1 receptor in human cancer - Arcaro, Alexandre (Frontiers in Pharmacology, 2013)
The insulin-like growth factor (IGF) signaling system plays a crucial role in human cancer and the IGF-1 receptor (IGF-1R) is an attractive drug target against which a variety of novel anti-tumor agents are being developed. Deregulation of the IGF signaling pathway frequently occurs in human cancer and involves the establishment of autocrine loops comprising IGF-1 or IGF-2 and/or IGF-1R over-expression. Epidemiologic studies have documented a link between elevated IGF levels and the development of solid tumors, such as breast, colon, and prostate cancer. Anti-cancer strategies targeting the IGF signaling system involve two main approaches, namely neutralizing antibodies and small molecule inhibitors of the IGF-1R kinase activity. There are numerous reports describing anti-tumor activity of these agents in pre-clinical models of major human cancers. In addition, multiple clinical trials have started to evaluate the safety and efficacy of selected IGF-1R inhibitors, in combination with standard chemotherapeutic regimens or other targeted agents in cancer patients. In this mini review, I will discuss the role of the IGF signaling system in human cancer and the main strategies which have been so far evaluated to target the IGF-1R.